NON-FINITE CLAUSES IN THE INTRODUCTION SECTION OF SKRIPSIS AND RESEARCH ARTICLES - Sarovah Widiawati (Institut Pendidikan Indonesia Garut, 2019)
Non-finite clauses are clauses which have no tenses. This study aimed to find the forms and functions of non-finite clauses in the introduction section of skripsis(ISoS) and research articles (ISoRA) in English field. Content analysis was used in this research. The ISoS and the ISoRA were selected randomly. The findings showed that there were three forms of non-finite clauses in the ISoS and ISoRA. In terms of functions, there were non-finite clauses as minor clause, qualifier, epithet, non-finite clauses as conjunction, non-finite clauses after conjunction, circumstance, prepositional phrase, actor, goal, carrier, attribute, possessive, identified, identifier, phenomenon, behaver, and existent. The ISoS were frequently presented in non-finite constructions as minor clauses and had more non-finite constructions in clause simples rather than clause complexes. The non-finite constructions in the introduction section of skripsisand research articles made the clauses dense.